Entrepreneurial motivations among female university youth in Saudi Arabia - Almobaireek, Wafa N.; Manolova, Tatiana S. (Journal of Business Economics and Management, 2013)
To successfully target potential women entrepreneurs in Saudi Arabia, a better understanding of their entrepreneurial motivations is needed. In this study, we used economic, human development, and social learning perspectives to explore the entrepreneurial motivations among female university youth in Saudi Arabia and formulated three hypotheses on the gender differences in these motivations. We conducted a survey among undergraduate students at King Saud University in Spring'2010 (n = 856) and tested our hypotheses using analysis of variance (chi-square tests and t-tests). Consistent with research on female entrepreneurs around the world, our results indicate that female university youth in Saudi Arabia are more likely than men to start an entrepreneurial venture out of necessity, whereas men are more likely to have a financial success motivation. At the same time, and in contrast to findings from studies on entrepreneurial motivations in the context of Western Europe and the USA, young Saudi university women report a narrower range of entrepreneurial motivations, compared to men. The implications of this exploratory study point to the need for initiatives specifically focused at young women in order to increase their confidence that entrepreneurship is a viable route to accomplish a broad range of career reasons.